Why did Donders, after describing pseudotorsion, deny the existence of ocular counterrolling together with Ruete, Volkmann, von Graefe and von Helmholtz, until Javal reconfirmed its existence?. (2nd October 2018) - Simonsz, H.J.; Wade, N.J.
ABSTRACT: After the rapid spread of strabismus surgery by total tenotomy, which had been proposed by the orthopedist Louis Stromeyer from Göttingen in 1838 and performed by the plastic surgeon Johann Friedrich Dieffenbach on October 26th and by the ophthalmologist Florent Cunier on October 29th, 1839, brilliant researchers studied the physiology of eye movements, resulting in the laws by Franciscus Cornelis Donders on pseudotorsion in tertiary positions of gaze and by Johann Benedict Listing that each eye position can be reached by rotation about an axis perpendicular to the primary and the new position of gaze. John Hunter had first described ocular counterrolling (OCR) with head tilt in 1786. The anatomist Alexander Friedrich von Hueck inferred from anatomical studies, however, that up to 28.6° OCR would be possible onhead-tilt to right or left shoulder in 1838, and estimated his own OCR seen in a mirror at approximately 25°. Donders, Christian Georg Theodor Ruete, Alfred Wilhelm Volkmann, Albrecht von Graefe and Hermann von Helmholtz subsequently denied the existence of OCR for many years and thought that only pseudotorsion existed. Louis Emile Javal had myopia and astigmatism, and he re-established the existence of OCR in 1867 when he noticed that, on head tilt to either shoulder, the axis of astigmatism of his eyes no longer coincided with the axis of astigmatism of his glasses.